Long-run performance of dye-sensitized solar cell using natural dye extracted from Costus woodsonii leaves - M. Z., Najihah; Noor, I. M.; Tan, Winie (Elsevier BV, 2022)
Current work explores the extract from Costus woodsonii leaves as a natural dye sensitizer for DSSC. The effect of solvent on pigment extraction is reported. The acetone is the optimal solvent to extract chlorophyll from C. woodsonii leaves. The presence of chlorophyll is evidenced from the FTIR and UV–Vis studies. The adherence of chlorophyll pigment to the TiO2 surface is supported by the XRD and FESEM. The performance of chlorophyll DSSC with gel-like PVdF-HFP based electrolyte has been investigated from the aspect of the thickness of the TiO2 mesoporous layer and extraction medium. The highest efficiency achieved is 0.65% with a short circuit current density of 2.25 mA cm⁻². The long-run performance of chlorophyll DSSC is monitored. The findings are discussed from the aspect of electron movement at the TiO2/dye interface.